Biofilm formation of Clostridium perfringens and its exposure to low-dose antimicrobials - Charlebois, Audrey; Jacques, Mario; Archambault, Marie (Frontiers in Microbiology, 2014)
Clostridium perfringens is an opportunistic pathogen that can cause food poisoning in humans and various enterotoxemia in animal species. Very little is known on the biofilm of C. perfringens and its exposure to subminimal inhibitory concentrations of antimicrobials. This study was undertaken to address these issues. Most of the C. perfringens human and animal isolates tested in this study were able to form biofilm (230/277). Porcine clinical isolates formed significantly more biofilm than the porcine commensal isolates. A subgroup of clinical and commensal C. perfringens isolates was randomly selected for further characterization. Biofilm was found to protect C. perfringens bacterial cells from exposure to high concentrations of tested antimicrobials. Exposure to low doses of some of these antimicrobials tended to lead to a diminution of the biofilm formed. However, a few isolates showed an increase in biofilm formation when exposed to low doses of tylosin, bacitracin, virginiamycin and monensin. Six isolates were randomly selected for biofilm analysis using scanning laser confocal microscopy. Of those, four produced more biofilm in presence of low doses of bacitracin whereas biofilms formed without bacitracin were thinner and less elevated. An increase in the area occupied by bacteria in the biofilm following exposure to low doses of bacitracin was also observed in the majority of isolates. Morphology examination revealed flat biofilms with the exception of one isolate that demonstrated a mushroom-like biofilm. Matrix composition analysis showed the presence of proteins, beta 1-4 linked polysaccharides and extracellular DNA, but no poly-beta-1,6-N-acetyl-D-glucosamine (PNAG). This study brings new information on the biofilm produced by C. perfringens and its exposure to low doses of antimicrobials.